Achieving reliable blood pressure measurements in clinical practice: It's time to meet the challenge - O'Brien, Eoin (J Clin Hypertens (Greenwich), 2018)
A summary of statements for blood pressure (BP) measurement in the evaluation of hypertension in the 21st century by 25 international experts is provided. The status of office, home and ambulatory BP measurement techniques are discussed. Office BP measurement, whether automated (preferred), or otherwise, should only be used as a screening measurement, and diagnostic decisions for the initiation and titration of drug treatment should be based on out‐of‐office measurements (ambulatory or home). The hardware and software requirements and the adaptations of BP measuring devices to record other cardiovascular functions, such as arrhythmias, and adaptations for smartphone use and for electronic transmission are discussed. Regulatory bodies are urged to make accuracy and performance assessment mandatory before marketing BP measuring devices. The legal implications of manufacturing inaccurate devices are noted.